2016
DOI: 10.1089/neu.2015.4278
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Bladder-Related Autonomic Dysreflexia after OnabotulinumtoxinA Treatment in Spinal Cord Injury

Abstract: Bladder-related events, including neurogenic detrusor overactivity, are the leading cause of autonomic dysreflexia in spinal cord injured individuals. Self-reported autonomic dysreflexia is reduced following onabotulinumtoxinA treatment for neurogenic detrusor overactivity; however, none of these trials have assessed autonomic dysreflexia events using the clinical cutoff of an increase in systolic blood pressure ≥20 mm Hg. This study used a prospective, open-labelled design from 2013 to 2014 to quantitatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…Given the potential of NDO to elicit AD, successful treatment of NDO could also have a positive effect on AD incidence and extent of related cardiovascular changes. In line with this hypothesis, Fougere et al [ 42 ] provided evidence of effectively reducing the frequency and severity of AD after intradetrusor onabotulinumtoxinA injections in patients with SCI. By improving LUT function and concurrently reducing cardiovascular responses to LUT stimuli, treatment of NDO appears to have the capacity to lower the risk for AD-related long-term complications.…”
Section: Discussionmentioning
confidence: 88%
“…Given the potential of NDO to elicit AD, successful treatment of NDO could also have a positive effect on AD incidence and extent of related cardiovascular changes. In line with this hypothesis, Fougere et al [ 42 ] provided evidence of effectively reducing the frequency and severity of AD after intradetrusor onabotulinumtoxinA injections in patients with SCI. By improving LUT function and concurrently reducing cardiovascular responses to LUT stimuli, treatment of NDO appears to have the capacity to lower the risk for AD-related long-term complications.…”
Section: Discussionmentioning
confidence: 88%
“…Fougere et al performed a study demonstrating the attenuation or elimination of hypertension due to AD in 17 persons with SCI during urodynamics before and after bladder chemodenervation [18]. That study also showed a similar result with ambulatory blood pressure monitoring outside of the urodynamics suite.…”
Section: Possible Mechanism Of Actionmentioning
confidence: 86%
“…Intravesical instillation with capsaicin, but not vehicle instillation, acutely worsened AD induced by bladder distention, but, one month later, it reduced bladder-related AD and urinary incontinence, suggesting that capsaicin-sensitive bladder afferents are involved in bladder-related AD (Igawa et al, 2003). A recent open-label clinical trial revealed that intradetrusor injections of onabotulinumtoxin-A decreased the severity and frequency of AD during urodynamics and during bladder-related events, and improved quality of life in patients with SCI (Fougere et al, 2016). In SCI rats, onabotulinumtoxin-A is also shown to reduce bladder-related AD in association with a decrease in bladder NGF expression (Elkelini et al, 2012).…”
Section: Discussionmentioning
confidence: 99%